A critical discourse analysis of senator Elizabeth Warren’s presidential campaign announcement speech = Phân tích diễn ngôn phê phán về bài phát biểu tranh cử tổng thổng của thượng nghị sĩ Elizabeth Warren - Trần, Hà Anh (2020)
This thesis examines the ideologies embedded in Senator Elizabeth Warren’s presidential campaign announcement speech in 2019 and the realizations of these ideologies through the lexical, grammatical, and structure of it. The transcript was retrieved from the website, Mass Live, and was personally checked for accuracy by a comparison of video recording of the speech provided by the reputable news source, C-SPAN. The speech was then systematically investigated following the Fairclough’s (2001) dialectical-relational approach towards Critical Discourse Analysis. There are two major ideologies presented. Firstly, the speech demonstrates the message of unity among American citizens under the leadership of Senator Warren to change America for the better. This ideology is manifested through the classification scheme, metaphors, the active voice, negative sentences, the personal pronoun “we”, and phrase repetition. Secondly, Senator Warren is a competent, qualified, and proud candidate to address numerous long-running inequalities and lead America towards a better future while wealthy people and the current Trump administration have been the cause of economic and societal injustice as well as corrupted political manipulation. This ideology is conveyed through the classification scheme, the meaning relations between words, the relational values of vocabulary, metaphors, the expressive values of vocabulary, the relational process, the passive voice, negative sentences, the personal pronoun “I”, auxiliary verb “can” and “will”, the expressive values of grammatical features, as well as the first seven parts of the larger-scale structure of the speech